Mangrove derived Streptomyces sp. MUM265 as a potential source of antioxidant and anticolon-cancer agents - Tan, Loh Teng Hern; Chan, Kok Gan; Pusparajah, Priyia; Yin, Wai Fong; Khan, Tahir Mehmood; Lee, Learn Han; Goh, Bey Hing (BMC, 2019)
Background: Colon cancer is the third most commonly diagnosed cancer worldwide, with a commensurately high mortality rate. The search for novel antioxidants and specific anticancer agents which may inhibit, delay or reverse the development of colon cancer is thus an area of great interest; Streptomyces bacteria have been demonstrated to be a source of such agents. Results: The extract from Streptomyces sp. MUM265 - a strain which was isolated and identified from Kuala Selangor mangrove forest, Selangor, Malaysia - was analyzed and found to exhibit antioxidant properties as demonstrated via metal-chelating ability as well as superoxide anion, DPPH and ABTS radical scavenging activities. This study also showed that MUM265 extract demonstrated cytotoxicity against colon cancer cells as evidenced by the reduced cell viability of Caco-2 cell line. Treatment with MUM265 extract induced depolarization of mitochondrial membrane potential and accumulation of subG 1 cells in cell cycle analysis, suggesting that MUM265 exerted apoptosis-inducing effects on Caco-2 cells. Conclusion: These findings indicate that mangrove derived Streptomyces sp. MUM265 represents a valuable bioresource of bioactive compounds for the future development of chemopreventive agents, with particular promise suggested for treatment of colon cancer. © 2019 The Author(s).